Pengaruh Kualitas Pelayanan Dan Harga Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pelanggan Ada Swalayan Semarang - Dheasey Amboningtyas; Leonardo Budi Hasiholan (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
This study aims to determine the effect of service quality and price on customer loyalty through customer satisfaction as an intervening variable in Semarang supermarket customers. The population in this study is the Customer / Self-Service Customer. In this study, the technique of the census method is taken, namely a technique that provides unequal opportunities or opportunities for each member of the population or all elements are selected as a census. that is, the total population can be used as the number of samples in this study, so that the census is determined to be 75 people. SPSS output shows that service quality variables partially have a positive and significant effect on customer satisfaction. The price variable partially has a positive and significant effect on customer satisfaction. Service quality variables partially have a positive and significant effect on customer loyalty. Price variables partially have a positive and significant effect on customer loyalty. Customer satisfaction variable partially has a positive and significant effect on customer loyalty. Customer satisfaction variables are not able to mediate the relationship between service quality and customer loyalty. Price variables are not able to mediate the relationship between price and customer loyalty.